2003
DOI: 10.1046/j.1365-263x.2003.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sociodemographic factors on dental anxiety in children seen in a suburban Nigerian hospital

Abstract: Further studies involving larger non-clinic samples are needed to examine the issues raised by the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 22 publications
2
57
1
11
Order By: Relevance
“…The socioeconomic status of each child was determined through a multiple-item scoring index [40] developed from information about the mother’s level of education and the father’s occupation. The index had been used in prior studies in Nigeria [41, 42]. Each child’s social class was classified as class I (upper class), class II (upper middle class), class III (middle class), class IV (lower middle class), or class V (lower class).…”
Section: Methodsmentioning
confidence: 99%
“…The socioeconomic status of each child was determined through a multiple-item scoring index [40] developed from information about the mother’s level of education and the father’s occupation. The index had been used in prior studies in Nigeria [41, 42]. Each child’s social class was classified as class I (upper class), class II (upper middle class), class III (middle class), class IV (lower middle class), or class V (lower class).…”
Section: Methodsmentioning
confidence: 99%
“…Total score can range from 15 to 75 points, and the intensity of patient's fear is proportional to the number of points. Patients who have 45 or more points are considered to be highly anxious patients 16,17 . Data were analyzed used STATISTICA for Windows, Release 5.5 A* and SPSS for Windows, Release 7.5**.…”
Section: Methodsmentioning
confidence: 99%
“…These studies show that oral health is also closely related to anxiety [18,33,34]. Folayan et al (2003) conducted a study with 81 children aged 8-13 years using the Child Fear Rating Scale-Dental Subscale (CFSS-DS), found that very few of the children had high level of dental anxiety as in 14.8% (n = 18) [34]. A systematic review of dental fear / anxiety and behavior problems by children and adolescents conducted by Klinberg and Broberg (2007) using the PUBMED database between 1982 and 2006 showed that 9% of children in Australia, Canada, Europe and the United States had dental fear / anxiety and behavior problems, and this frequency was found to increase with age.…”
Section: Discussionmentioning
confidence: 87%
“…These studies show that oral health is also closely related to anxiety [18,33,34]. Folayan et al (2003) conducted a study with 81 children aged 8-13 years using the Child Fear Rating Scale-Dental Subscale (CFSS-DS), found that very few of the children had high level of dental anxiety as in 14.8% (n = 18) [34].…”
Section: Discussionmentioning
confidence: 99%